Assessment of Hypoxemia using Downes Score in Neonates with Respiratory Distress - Shrestha, Sabina; Shrestha, Sujit Kumar; Shrestha, Gentle Sunder; Dhakal, Madhu Sudhan (Nepal Medical College Journal, 2021)
Respiratory distress in newborn is a common problem leading to hypoxemia. Pulse oximetry is the tool for measuring oxygen saturation noninvasively and blood gas analysis is the gold standard for oxygen monitoring. Downes score can be used as an alternative to assess respiratory distress clinically and determine the need of oxygen supplementation when these facilities are not available. This study was done to evaluate the validity of Downes score to assess hypoxemia in newborn with respiratory distress. This is a cross sectional descriptive study conducted from June 2020 to February 2021 in Neonatal Intensive Care Unit of Nepal Medical College Teaching Hospital. Oxygen saturation of newborn with respiratory distress was measured by pulse oximetry. At the same time the neonate was assessed for respiratory distress clinically using Downes score. Downes score and oxygen saturation measured by pulse oximetry were compared. Hypoxemia was defined as oxygen saturation less than 90% in term/ post term newborn and less than 88% in preterm baby. Similarly, neonate was considered to be hypoxic when Downes score was ≥5. The accuracy of Downes score was assessed by its sensitivity and specificity in detecting hypoxemia. Altogether 121 neonates were included in the study. Sensitivity and specificity of Downes score of 5 was 94.12% and 93.10% respectively. In conclusion, Downes score can be used as a clinical diagnostic means for assessing hypoxemia in neonates with respiratory distress